Women Psychotherapists : Journeys in Healing. - Comas-Diaz, Lillian; Weiner, Marcella Bakur (Jason Aronson, 2011)
This book describes the real-life journeys of women psychotherapists: why each woman chose this profession and what she learned about others--and most importantly, about herself--in this choice. Most critically, these women now share how they have integrated this wisdom into their everyday lives. While psychotherapists may also be authors, few write books about their journeys in the profession. Women Psychotherapists: Journeys in Healing is one of those rare books. Each contributor invites her readers onto the road traveled by the woman who listens to others needing her help and guides them into living a more joyous, successful life, even as she moves towards greater fulfillment in her own life.